MODEL BIMBINGAN KELOMPOK UNTUK MEMBANTU SISWA MEMPERSIAPKAN DIRI MENGHADAPI PERNIKAHAN DAN BERKELUARGA BERDASARKAN PENDEKATAN PERKEMBANGAN - Farida, Euis (2010)
This study conducted based on some empirical studies that showed various behavior symptoms of adolescents indicating existence of obstacles for achieving developmental tasks of the adolescents, namely, in preparing themselves to face marriage and to have family. One of phenomena that appear then was misconduct of sexual behavior of some senior high school students. The phenomena may not be ignored. There should be real,integrative, systematic, and simultaneousefforts conducted by various sides including school counselors in order thatthe students are able to achieve their developmental tasks in facing marriage and having a family. The study aimed at examining a group guidance model for helping students prepare themselves to face marriage and to have family based on developmental approach. The research used research and development approach with qualitative and quantitative methods. Mixed method design sequence was chosen. It had four steps covering preliminary study, model development, model rational validation, and model empirical validation. Results of the study showed that students' readiness in facing marriage and having family categorized into upper medium. There were four factors hampering the readiness comprising (1) characteristics of students' personality; (2) school environment; (3) family environment; and (4) society environment. Results of rational and empirical validations indicated that developmental guidance model was effective to help students prepare themselves to face marriage and to have family. The researchrecommended that the group guidance model for helping students prepare themselves in facing marriage and having a family based on developmental approach can be implemented by counselors at schools.